Facile synthesis of highly active Pd nanocatalysts using biological buffers - Janairo, Jose Isagani B. (Animo Repository, 2017)
A simple and straightforward approach in the synthesis of highly active palladium nanocatalysts aided by biological buffers is herein presented. Using HEPES and Tris as the buffers, highly active sub-10 nm palladium nanoparticles were formed. These nanocatalysts exhibited high catalytic activity toward the reduction of nitroaminophenol isomers. Moreover, this approach involves ambient conditions and a one-pot setup void of harsh reagents. The presented method highlights practicality without compromising catalytic activity which is very attractive for routine preparation of palladium nanocatalysts.